Manajemen Persediaan Obat yang Efisien melalui Sistem Berbasis Web pada Griya Syifa’ul Linnas Bekasi - Khoerunnisa Nuroktaviani; Dwi Ismiyana Putri (Bahasa Indonesia, 2022)
Griya Syifa'ul Linnas is a cupping and iridiology health house which also provides various kinds of herbal medicines. In the activities of recording drug supplies, it is still done manually, such as collecting bills for buying drugs, recording the availability of drugs using a book. While the available medicines consist of various types, so they have several obstacles in terms of recording calculation errors, delays in preparing drug inventory reports caused by the accumulation of incoming and outgoing drug transaction data. If it is done manually continuously, it will cause data to be lost and damaged and it will take quite a long time to find information and check the availability of drugs. This research aims to help Griya in the process of recording and checking the availability of drugs. The proposed system was developed using the Rapid Application Development (RAD) method. This website is based on a MySql database design and uses the PHP programming language. From this research, it can produce a website-based drug inventory information system that can be the right solution to handle incoming and outgoing drug transaction activities, produce accurate drug inventory reports, and help the process of monitoring drug inventory at Griya Syifa'ul Linnas to be more effective and efficient.